Author accepted manuscript: spelling ability influences early letter encoding during reading: Evidence from return-sweep eye movements - Parker, AJ; Slattery, T (SAGE Publications, 2020)
In recent years, there has been an increase in research concerning individual differences in readers’ eye movements. However, this body of work is almost exclusively concerned with the reading of single-line texts. While spelling and reading ability have been reported to influence saccade targeting and fixation times during intra-line reading, where upcoming words are available for parafoveal processing, it is unclear how these variables affect fixations adjacent to return-sweeps. We, therefore, examined the influence of spelling and reading ability on return-sweep and corrective saccade parameters for 120 participants engaged in multiline text reading. Less-skilled readers and spellers tended to launch their return-sweeps closer to the end of the line, prefer a viewing location closer to the start of the next, and made more return-sweep undershoot errors. We additionally report several skill-related differences in readers’ fixation durations across multiline texts. Reading ability influenced all fixations except those resulting from return-sweep error. In contrast, spelling ability influenced only those fixations following accurate return-sweeps—where parafoveal processing was not possible prior to fixation. This stands in contrasts to an established body of work where fixation durations are related to reading but not spelling ability. These results indicate that lexical quality shapes the rate at which readers access meaning from the text by enhancing early letter encoding, and influences saccade targeting even in the absence of parafoveal target information.